Physico-Chemical Properties and Deposition Potential of PM2.5 during Severe Smog Event in Delhi, India - Fatima, Sadaf; Mishra, Sumit Kumar; Ahlawat, Ajit; Dimri, Ashok Priyadarshan (My University, 2022)
The present work studies a severe smog event that occurred in Delhi (India) in 2017, targeting the characterization of PM2.5 and its deposition potential in human respiratory tract of different population groups in which the PM2.5 levels raised from 124.0 µg/m3 (pre-smog period) to 717.2 µg/m3 (during smog period). Higher concentration of elements such as C, N, O, Na, Mg, Al, Si, S, Fe, Cl, Ca, Ti, Cr, Pb, Fe, K, Cu, Cl, P, and F were observed during the smog along with dominant organic functional groups (aldehyde, ketones, alkyl halides (R-F; R-Br; R-Cl), ether, etc.), which supported potential contribution from transboundary biomass-burning activities along with local pollution sources and favorable meteorological conditions. The morphology of individual particles were found mostly as non-spherical, including carbon fractals, aggregates, sharp-edged, rod-shaped, and flaky structures. A multiple path particle dosimetry (MPPD) model showed significant deposition potential of PM2.5 in terms of deposition fraction, mass rate, and mass flux during smog conditions in all age groups. The highest PM2.5 deposition fraction and mass rate were found for the head region followed by the alveolar region of the human respiratory tract. The highest mass flux was reported for 21-month-old (4.7 × 102 µg/min/m2 ), followed by 3-month-old (49.2 µg/min/m2 ) children, whereas it was lowest for 21-year-old adults (6.8 µg/min/m2 ), indicating babies and children were more vulnerable to PM2.5 pollution than adults during smog. Deposition doses of toxic elements such as Cr, Fe, Zn, Pb, Cu, Mn, and Ni were also found to be higher (up to 1 × 10−7 µg/kg/day) for children than adults.
Keywords: PM2.5; Chemical composition; morphology; deposition potential; smog; health effects